Combating Forest Malaria: a major challenge in eliminating Malaria in Bangladesh (Bangladesh Journal of Zoology, 2024)
Malaria is a major public health concern in tropical and subtropical areas including Bangladesh. The country has a long history of incurring high malaria morbidity and mortality in a heterogeneous transmission dynamics- demographical, spatial, and temporal. Elimination of malaria in Bangladesh remains a prerequisite for promoting better public health, especially in the malaria hotspots in its remote south-east and north-east border areas. The country boasts with the world's largest delta and lengthy monsoons sharing her border with India and Myanmar- additional two endemic countries for malaria in the SEA.With a significant progress in combating malaria in recent past, Bangladesh now envisages to eliminate the disease by 2030. A significant decline in malaria cases and deaths in its plain areas, however is intrigued with in-country as well as cross-border human movement to and from the forests in and around Chattogram Hill Tracts that reportedly works as a source of infections of the disease. This forest malaria remains a significant obstacle to the country’s malaria elimination efforts.Bangladesh J. Zool. 52(1): 03-25, 2024